Briggsia hastingsi, a new genus and species of clingfish from Oman - Craig, Matthew T.; Randall, John E. (Zootaxa, 2009)
Briggsia hastingsi is described as a new genus and species of gobiesocid fish from a single specimen, 22 mm in standard length, collected in 2 m depth on the southeastern coast of Oman. The genus differs principally from other aspasmine genera in having fewer dorsal- and anal-fin rays (4 each) and a shorter head (head length 2.5 in standard length).